Flexural design of concrete beams reinforced with FRP rebars - Barbosa,Felipe Augusto da Silva (2023)
Abstract The corrosion of steel rebars is the main cause of reinforced concrete degradation, which results in increasing costs with structural rehabilitation and repairs. As a solution, corrosion resistant rebars, such as those of FRP – Fiber-reinforced polymer –, have been used to replace conventional steel. This paper describes the development of a design program that calculates the flexural FRP reinforcement of T-shape beams. The possibilities as regards the neutral axis position, failure mode and concrete linear or non-linear behavior define the design scenarios for which their respective equations were deduced. The flexural strengths computed using the deduced equations showed agreement with experimental results for 125 beams, validating the proposed methodology. Since FRP rebars are vulnerable to creep rupture, the sustained stresses must be lower than the maximum allowed by ACI 440.1R-15, which may require increases in areas, modifying the flexural strength. Therefore, the equations to compute the new neutral axis depth and flexural strength based on the adjusted area were deduced and implemented in the computational program. Subsequently, this paper presents design examples considering all scenarios for which the equations were deduced. The design of one T-section considering different FRP rebars combined to normal and high-performance concretes is also reported. The results showed that beams reinforced with aramid and glass FRP required large areas to avoid creep rupture, whereas the areas of those reinforced by carbon FRP rebars were considerably small; however, they exhibited small curvatures and fragile failure when under-reinforced.